Perceptual consequences of change in vocoded speech parameters for various reverberation conditions - Drgas, Szymon; Błaszak, Magdalena (Archives of Acoustics, 2007)
The perceptual consequence of change in parameters of vocoded speech for various reverberationconditions has been examined. The three controlled variables were: number ofbands, instantaneous frequency changes rate and reverberation conditions. The effects werequantified in terms of: (a) non-words’ recognition scores for young normal-hearing listeners,(b) “ease of listening” based on the time of reaction (response delay) and (c) the subjectivemeasure of difficulty (ten-degree scale). The results have shown that the fine structure informationis a relevant cue in speech perception in reverberation conditions. It has also beenobserved that only the slow variations of instantaneous frequency are critical in perception.A good correlation between all subjective measures considered was found in this study.